1977
DOI: 10.1159/000260269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Acquired Pellicle and of Dental Plaque on the Implantation of Streptococcus mutans on Tooth Surfaces in Man

Abstract: Streptomycin (SM)-resistant Streptococcus mutans was implanted onto individual tooth surfaces by the topical application of heavy cell suspensions in buffer. The presence of an acquired pellicle or of 2-day-old dental plaque decidedly impaired implantation; the recovery of implanted, SM-resistant S. mutans was greatest when the labelled cells were applied directly on newly cleansed tooth surfaces. Even though S. mutans constituted only a very small proportion of the bacteria on each tooth surface, the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…The kind and amount of bound salivary components in turn may influence the colonisation of these surfaces by different micro-organisms, for instance by Streptococcus mutans on teeth [31,36,38,45], which is a known prerequisite for caries, or by Candida albicans on mucosal surfaces, which is responsible for denture stomatitis [10]. Colonisation and growth of these micro-organisms also takes place on artificial surfaces such as dental materials, but with somewhat different properties [10,30], from where they may spread to the teeth or mucosal areas.…”
Section: Introductionmentioning
confidence: 99%
“…The kind and amount of bound salivary components in turn may influence the colonisation of these surfaces by different micro-organisms, for instance by Streptococcus mutans on teeth [31,36,38,45], which is a known prerequisite for caries, or by Candida albicans on mucosal surfaces, which is responsible for denture stomatitis [10]. Colonisation and growth of these micro-organisms also takes place on artificial surfaces such as dental materials, but with somewhat different properties [10,30], from where they may spread to the teeth or mucosal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Liljemark and Schauer [1977] demonstrated increased ad sorption of S. sanguis and S. mitis cells to saliva-coated apatite, when compared to ad sorption to untreated apatite, although the adsorption of 5. mutans cells was unaffect ed. Ruangsri and Orstavik [1977] reported that, in vivo, the acquired pellicle actually impaired implantation on newly cleaned tooth surfaces. Clark et al [1978] showed that saliva pretreatment increased the affini ty of hydroxyapatite beads for cells of S. mutans even though the total number of ad sorption sites on the beads was considerably reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The effector strain was also designed to produce elevated levels of a novel peptide antibiotic, mutacin1140, giving it a strong advantage over competing strains of S. mutans. Previous attempts to re-colonize the oral flora with less pathogenic bacteria had failed due to the resistance of the resident S. mutans strains to the colonizers [27,30,41,50].…”
Section: Introductionmentioning
confidence: 99%